Structural and Metabolic Changes in Pregnant Rat Uterine and Adipose Tissue Induced by a High-Fat High-Sugar Diet - Dina Šišljagić; Senka Blažetić; Milorad Zjalić; Irena Labak; Vedrana Ivić; Kálmán Ferenc Szűcs; Róbert Gáspár; Eszter Ducza; Sandor G. Vari; Andrijana Muller; Marija Heffer (Biomolecules)
Pregnancy presents specific metabolic demands, and disruption caused by a high-fat high-sugar diet (HFHSD) have been associated with significant complications, including maternal health risk, fetal developmental issues, and infertility. Obesity-related changes in the uterine tissues may contribute to these challenges. This study analyzed structural changes in the uterus and adipose tissue of pregnant rats on gestation day 22 fed an HFHSD using various staining techniques. Hematoxylin and eosin staining showed morphological changes in the adipose tissue and the uterine structure, including the lumen size and the thickness of the myometrium, endometrium, and perimetrium. The amount of collagen in the uterus was determined by PicroSirius red staining, while PAS-D staining was used to observe glycogen content. Key protein expressions, such as insulin and leptin receptors and UCP1 and UCP3, were analyzed by immunohistochemistry. The HFHSD promoted hypertrophy of visceral and gonadal adipocytes, suggesting metabolic alterations. By the end of pregnancy, a significant reduction in uterine lumen size was observed. Additionally, a decrease in insulin and higher leptin receptor expressions in the myometrium indicated significant physiological alteration. These findings offer insight into how an HFHSD affects uterine structure and function during late pregnancy but should be interpreted within the physiological context of gestation-related metabolic changes. Further research is needed to understand the functional consequences of these alterations on reproductive and metabolic health.